2021
DOI: 10.3390/rs13122320
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-1 Backscatter Analysis and Radiative Transfer Modeling of Dense Winter Wheat Time Series

Abstract: This study evaluates a temporally dense VV-polarized Sentinel-1 C-band backscatter time series (revisit time of 1.5 days) for wheat fields near Munich (Germany). A dense time series consisting of images from different orbits (varying acquisition) is analyzed, and Radiative Transfer (RT)-based model combinations are adapted and evaluated with the use of radar backscatter. The model shortcomings are related to scattering mechanism changes throughout the growth period with the use of polarimetric decomposition. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Focusing on agricultural areas, predominantly located on flat surfaces, the influence of the azimuth angle is substantially lower [71]. Via the investigation of the influence of azimuthal angle over winter wheat fields, it was found negligible within a dense time series [72].…”
Section: Incidence Angle Normalizationmentioning
confidence: 93%
See 1 more Smart Citation
“…Focusing on agricultural areas, predominantly located on flat surfaces, the influence of the azimuth angle is substantially lower [71]. Via the investigation of the influence of azimuthal angle over winter wheat fields, it was found negligible within a dense time series [72].…”
Section: Incidence Angle Normalizationmentioning
confidence: 93%
“…Furthermore, the estimated soil moisture still showed extreme low and high values due to the incidence angle still effect present in the backscatter time series. Crop-dominated stations showed significant variation in correlation and error between individual years due to the influence of incidence angle, which depends on plant geometry, plant phase, and vegetation water content, changing both between the year as well as within a year [72,84]. In contrast, the soil moisture estimation at the meadow station (RU_C_005) is stable over the years, with only slight changes in correlation and uRMSE.…”
Section: Effect Of Individual Processing Steps On Soil Moisture Estim...mentioning
confidence: 99%
“…These results also strengthened the findings in [7,8], which showed that the VH/VV ratio is important in accessing soil moisture. Works [13,14] discuss the importance of correctly handling the variations in Sentinel-1 incident angles for any Radiative Transfer (RT)-based model. Similarly, Refs.…”
Section: State Of the Art And Challengesmentioning
confidence: 99%
“…and the SAR wavelength [24]. For certain crops, such as wheat and barley, several studies have demonstrated that the sensitivity of the C-band SAR signal (wavelength ~6 cm) to soil moisture is negligible in the presence of very well-developed vegetation cover [25][26][27][28][29][30]. El Hajj et al [25] showed that for wheat crops, the C-band S1-SAR signal in VV and VH polarizations becomes insensitive to surface soil moisture for LAI (Leaf Area Index) values beyond 1.5 m 2 /m 2 (vegetation height of approximately 70 cm).…”
Section: Introductionmentioning
confidence: 99%